KAIDAH FONOTATIK BAHASA MUNA - Laode Kunu (Multilingual, 2016)
A primary issue in this study is a rule phonotactics in Muna language. This study aimed to describe the rulesphonotactics of syllable and word in Muna language. The method used in this research is descriptive qualitativemethod. The use of this method is intended to systematically and accurately describe the characteristics andproperties of natural language data Muna and relationship of phenomena in the data and resulting desriptionof actual data. Method applied is a method of data collection and methods refer to a conversation. Referto the method is done by listening to the use of language by tapping techniques, refer to the technical note,recording technique and technique of introspection. Furthermore, data analysis using a unified assessmentand distributional methods. The use of these techniques meant that the problems associated with the toolsstudied determinants that are beyond the language in question and which are in the languages concerned.Furthermore, this technique is conducted with the following steps: (1) making a prediction probability distribution of phonemes based on the number of phonemes in a language Muna, both in its level of syllables and words; and (2) looking for evidence of the existence of the distribution of data sources in order to obtainthe rules of substitution and permutation fonotatik with phonemes. The results showed that out of 200 inBM Swadesh vocabulary found as many as 56 or 28% said syllable pattern V and as many as 199 or 99.5%patterned silabe KV. Furthermore, the rules fonotatik words with vowels with vowels with 14 words or around56% collocation of V-V and not found as much as 11 or 44%; collocation of vowel-consonant there are 91 orabout 73% and is not found as many as 34 or 27% collocation of V-K; and consonants collocation with vowelsare 102 or as much as 82% collocation of K-V and not found as much as 23 or 18%.